2001
DOI: 10.1016/s1525-1578(10)60647-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction Detection of Kaposi's Sarcoma-Associated Herpesvirus-Optimized Protocols and Their Application to Myeloma

Abstract: Since its discovery in 1994, KSHV (also called human herpesvirus-8 or HHV8) has been implicated in a variety of disorders. Although the association of KSHV with Kaposi's sarcoma (KS), primary effusion lymphoma (PEL), and multicentric Castleman's disease has been well established, its presence in some other diseases, such as multiple myeloma, remains controversial. Because most KSHV studies are based on polymerase chain reaction (PCR) analysis, the conflicting data may be attributable to variations in the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
2
42
1
Order By: Relevance
“…As we found no viral DNA, it was not surprising that all our cases were negative for latent nuclear antigen, corroborating the immunohistochemical findings on inflammatory myofibroblastic tumor from varying sites reported by Yamamoto et al 22 and pediatric cases reported by Mergan et al 23 Molecular identification of HHV-8 is known to produce both false-positive and false-negative results. [24][25][26] The latter is thought, in part, to be related to HHV-8 sequence variation, which can range up to 35% in certain regions of the viral genome, as in ORFK1. 26 The use of a single primer set based on a sequence with a high level of sequence variation can lower the PCR sensitivity and, therefore, the rate of HHV-8 detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we found no viral DNA, it was not surprising that all our cases were negative for latent nuclear antigen, corroborating the immunohistochemical findings on inflammatory myofibroblastic tumor from varying sites reported by Yamamoto et al 22 and pediatric cases reported by Mergan et al 23 Molecular identification of HHV-8 is known to produce both false-positive and false-negative results. [24][25][26] The latter is thought, in part, to be related to HHV-8 sequence variation, which can range up to 35% in certain regions of the viral genome, as in ORFK1. 26 The use of a single primer set based on a sequence with a high level of sequence variation can lower the PCR sensitivity and, therefore, the rate of HHV-8 detection.…”
Section: Discussionmentioning
confidence: 99%
“…24 False-positive results are thought to be due to utilization of high cycle protocols and/or complimentary primer sets, as in nested PCR. Through a set of validation tests, Pan et al, 25 demonstrated that nested PCR is readily contaminated, even in strictly controlled environments, and use of standard PCR with more than one set of primers is recommended. In their study, 6 of 16 negative controls tested positive for HHV-8 sequences in nested PCR using primers to ORF26, but none were positive utilizing standard PCR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study by Pan and coworkers (28), the authors concluded that KSHV detection by PCR may involve a high rate of false-negative results. For this reason, optimization of PCR procedures is mandatory, and nested-PCR approaches as well as amplification of different segments of the KSHV genome are recommended in order to obtain accurate results (28). Using a standard PCR procedure to detect the KSHV genome in DNA from formalin-fixed paraffinembedded tissue from few cases, Caterinode-Araujo et al (25) initially found the virus in 3/7 (42.9%) KS cases; however, all of their samples were found to be positive after nested-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The samples without amplification in this first PCR assay were used in ORF26-directed nested-PCR (28). Doubtful cases were analyzed for amplification of viral ORF72 segment, which encodes a viral capsid protein (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation